A total systems study on RickiMel Marketing Corporation - Bernardo, Nathania Faye A.; Rodriguez, Raisa R.
RickiMel Food Company was founded in 1996 by Mr. Ricardo C. Gines, Mrs. Emilia A. Gines, and Mr. Arnold A. Caliboso. The company started off as a manufacturer and distributor of its own chicken breading mix to various wet and dry supermarkets. In 2003, the company ventured into marketing and distributing products of other brands such as Ideal, Super Q and Mama Sita's. The company became the distributor of their products in different supermarket chains. It was during this time that another section of the company was born, the Rickimel Marketing Co. Eventually, Rickimel Food Co. was absorbed as a joint company with the Rickimel Marketing Co. In 2011, the name Rickimel Food Co. was changed to Hapimi Food Co. in preparation for the release of a rebranded line of products. Today, the company continues to expand and improve their products by enhancing the formulation, creating new labels, venturing into events, entering big supermarkets such as Puregold and considering mergers with manufacturers of leading brands of food products in different regions nationwide. The owners of the company have consulted with the group their present company concerns. With that, the group documented the current systems of the company and confirmed which concerns were costing the company most. After documenting the current systems of the company, the proponents learned that during the last half of 2014, Rickimel lost approximately 1,224,285.39 which is 2.65% of its total intended sales due to product stock out. Product stock out of Hapimi products occurs usually during the peak seasons (November-January and March-May). Product stock out is mostly caused by the breakdown of the fryers which is used in the production of Hapimi products. The marketed goods of Rickimel experiences product stock out as well due to the inability of some of their clients to deliver their products on time. For the same time period, Rickimel was behind by 8.8%, approximately Php 4,027,904. 72, of its total intended sales due to cancelled deliveries arising from the inability of customers to settle their payments during delivery. Customers are unable to settle their payment because they forgot the goods were supposed to be delivered on the said date or the money intended for the payment were used for something else. Although the undelivered products are not considered as a loss yet since it can still be sold for the next day, the supposedly total sales amount for a given day is not reached since the undelivered items are returned to the warehouse instead of being sold to other stores within the delivery area. Frequent breakdown of fryers in the commissary has also contributed to Hapimi product stockout. This is due to unregulated maintenance of equipment. The company only applies corrective maintenance, but seldom conducts preventive maintenance on its equipment. The company cannot afford having frequent breakdown of equipment, especially during peak season, as it will only aggravate the occurrence of product stockout. Absenteeism and tardiness of workers, especially of the drivers, in Rickimel results to delays and cancellation of deliveries. The rate increases especially after payday. Although the management has implemented penalties for workers who do not report to work without a valid reason, these are not strictly observed due to poor documentation of employee attendance. This may also incur additional costs for the company as they may be paying for workers who did not actually report to work. With the goal of improving the company's operations, the proponents developed several different strategies. For each major problem, a strategy (or several) was made. The table below summarizes these strategies. These strategies were then evaluated based on its ability to address the key issues, contribution to operation cost reduction, ease of implementation, and cost of implementation. After which, based on the results of the evaluation of alternatives (strategies), the proponents recommended that the company implement the asterisked strategies above. These were (1) Order Confirmation - confirm the orders ahead of the scheduled delivery time to lessen the instances of cancelled deliveries, (2) Van Salesman - task of the van salesman is to offer and sell the products from the cancelled delivery to other customers and non-customers within the area, and (3) Implement Regular Preventive Maintenance Procedure. With these, the proponents hope that the Rickimel's system will improve and in turn, improve its operations, thus, raising the company's overall profits.